Variable comprehensive coefficient draft-position integrated tillage depth control method of tractor based on traction resistance interval division - Sun, Xiaoxu; Song, Yue; Wang, Lin; Lu, Zhixiong; Qian, Jin; Wang, Tao (International Journal of Agricultural and Biological Engineering, 2025)
Aiming at the problem that the draft-position integrated tillage depth control method with fixed comprehensive coefficient of tractor electro-hydraulic hitch system is difficult to adapt to the working environment with large changes in soil conditions, a tractor draft-position integrated tillage depth control method with variable comprehensive coefficient was proposed. A comprehensive coefficient control scheme based on traction resistance was designed and its working principle was clarified. Aiming at the time-varying tillage depth control system, a tillage depth control algorithm based on the sliding mode control with differential observer was designed. In order to verify the performance of the control scheme, a control system simulation model and a bench test platform were built, and the performance was compared with the draft-position integrated control method with fixed comprehensive coefficient of 0.5. The results showed that the variable comprehensive coefficient tillage depth control method can automatically adjust the comprehensive coefficient according to the change of soil conditions, and has higher traction efficiency. In the small resistance range, it can better ensure the quality of operation; in the large resistance range, it can ensure the engine performance and protect the tractor from damage. This method is more adaptable to the complex field operation environment, which provides a reference for the research of tillage depth control method. Key words: tractor; variable comprehensive coefficient; draft-position integrated tillage depth control; traction resistanceDOI: 10.25165/j.ijabe.20251806.9394Citation: Sun X X, Song Y, Wang L, Lu Z X, Qian J, Wang T. Variable comprehensive coefficient draft-position integrated tillage depth control method of tractor based on traction resistance interval division. Int J Agric & Biol Eng, 2025; 18(6): 66–74.